Da Gud blev til en lille grøn mand fra Rummet - Rothstein, Mikael (Religionsvidenskabeligt Tidsskrift, 1992)
The International Raëlian Movement, founded by the French journalist Claude Vorlihon (Raël) in 1974, is one of the best consolidated UFO-cults, now present in more than 40 countries. Its teaching is primarily derived form the judeo-christian mythology, although the interpretation throughout is related to modern scientific and pseudo-scientific notions. Further the cult integrates elements of European folklore, which indeed makes it a syncretistic religion. The article describes the teaching of Raël (said to be the Messiah), and points the the fact that no new religious ideas or structures are promoted. Rather a well-known set of ideas is reinterpreted in the syncretisticc process. The structure of traditional religion is maintained, but the actors on the mythological stage are new. God or even "the divine" is not recognized. We are facing an atheistic religion which claims that the technology and science of extraterrestrial beings are responsible for life of Earth. The article attempts to show how this transfer from transcendent God to extraterrestrial humanoid are dealt with within the limits of already existing mythological structures.